THE EFFECTIVENESS OF HOLISTIC MASSAGE TRAINING ON IMPROVING POSYANDU CADERS KNOWLEDGE AND SKILLS IN HANDLING SPEECH DELAY IN TODDLER - Rita Kamalia; Nimas Nabila Khoirunisah; Selly Marshela; Della Agustina H.R; I Gusti Ayu Putu Desy Rohana (LPPM STIKES Al-Ma'arif Baturaja, 2025)
Posyandu cadres play a vital role in the early detection and intervention of speech delay in toddlers. This study aims to evaluate the effectiveness of holistic massage training in improving the knowledge and skills of posyandu cadres in managing toddlers with speech delay. This research is an experimental qualitative study employing a pre-experimental one-group pre-test and post-test design. The study sample consisted of 30 posyandu cadres from the villages of Muara Lawai, Tanjung Jati, and Lubuk Ampelas. The intervention was delivered in the form of training sessions held three times, each lasting 90 minutes, conducted during August 2024. Instruments used included a knowledge questionnaire and a skills observation checklist, both administered before and after the training. Data analysis using the Paired Sample T-Test showed a significant increase in knowledge from an average of 50.72% to 80.90%, and in skills from 15.50 to 25.50 (p < 0.05). These findings indicate that holistic massage training significantly enhances the capacity of posyandu cadres in handling speech delay. The training is recommended as an effective community-based intervention strategy to improve the quality of detection and stimulation of speech development in toddlers.